The Papacy as ecumenical challenge : contemporary Anglican and Protestant perspectives on the Petrine Ministry - Le Bruyns, Clint (Stellenbosch : University of Stellenbosch, 2007)
Thesis (DTh (Systematic Theology and Ecclesiology))--University of Stellenbosch, 2004.